2018
DOI: 10.1371/journal.pone.0206617
|View full text |Cite
|
Sign up to set email alerts
|

Waist, neck circumferences, waist-to-hip ratio: Which is the best cardiometabolic risk marker in women with severe obesity? The SOON cohort

Abstract: A centralized deposit of adiposity increases the risk of cardiometabolic diseases. Several anthropometric markers can be used to characterize fat distribution. In the case of severe obesity, several markers, such as hip and waist circumference, are prone to measurement error. Conversely, neck circumference is easy to obtain. The aim was to determine the best surrogate marker of obesity-related cardiometabolic diseases from: body mass index (BMI), waist, hip and neck circumferences and waist-to-hip ratio.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 49 publications
6
46
0
3
Order By: Relevance
“…According to our results, higher values of WHiR were associated with shorter sleep duration, lower sleep efficiency and increased time awake after sleep onset. These results are in accordance with previous research emphasizing that, besides being major risk factors for cardiometabolic alterations, cancer and all-cause mortality [58,59], WHiR and abdominal obesity are significantly related to severe sleep disturbances such as short sleep duration and obstructive sleep apnoea [23,60], especially in younger adults [58]. Regarding LMI, we found that those participants with higher LMI exhibited shorter sleep and lower sleep efficiency.…”
Section: Discussionsupporting
confidence: 92%
“…According to our results, higher values of WHiR were associated with shorter sleep duration, lower sleep efficiency and increased time awake after sleep onset. These results are in accordance with previous research emphasizing that, besides being major risk factors for cardiometabolic alterations, cancer and all-cause mortality [58,59], WHiR and abdominal obesity are significantly related to severe sleep disturbances such as short sleep duration and obstructive sleep apnoea [23,60], especially in younger adults [58]. Regarding LMI, we found that those participants with higher LMI exhibited shorter sleep and lower sleep efficiency.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, neck circumference is also related to oxidative stress, endothelial cell dysfunction and vascular injury24 31 32 and it is correlated with visceral adipose tissue, as measured by CT 30 34 35. Therefore, neck circumference seems to be an important anthropometric marker to identify patients with a high cardiometabolic risk 36…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, low adipokine production in response to IH might reflect a greater propensity for ectopic and visceral fat deposition in patients with OSA. In overweight males, after controlling for confounders, OSA is specifically associated with a higher amount of visceral adiposity whereas in females, OSA is associated with global adiposity [53,54]. Independently of BMI, OSA is involved in the development of ectopic fat depots contributing to the progression of insulin resistance in the different metabolic organs, including the pancreas, liver and muscle (figure 2) [23,24,55].…”
Section: Adipose Tissue and Ih: Insight From Rodent And Reductionist mentioning
confidence: 99%